Sustainable practices for MICE tourism from the perspectives of convention centre in Terengganu / Maisarah Abdul Hamid, Zatul Iffah Mohd Fuza and Razlan Adli Zain - Abdul Hamid, Maisarah; Mohd Fuza, Zatul Iffah; Zain, Razlan Adli (2012)
Malaysia nowadays is being accepted as one of the top destination for meeting, incentives, convention and exhibition (MICE) tourism. It has attracted both local and foreign tourist to participate in one of this tourism sectors. The issues of sustainable development are growing trends in many industries including tourism. The papers will focus on the sustainable development in the MICE tourism practices. The objective of this paper is to look at the development of MICE industry in Terengganu. In addition, this paper aims to look the sustainable concept that suitable to be implementing for MICE tourism. A questionnaire will be used to collect the data to look at the sustainable practice that used in the MICE venue. Other than that, data will be collected using the secondary data to collect information about MICE industry in Malaysia. The result of this study is useful to provide recommendation on the suitable sustainable practices in the MICE industry.